Country Risk Modeling Using Bayesian Network - Asadi Ghajarloo, Siavash (2010)
This project aims to predict risk level of country in order to prepare appropriate information for investors. To achieve this goal, this research is using 186 articles which are political news about Pakistan as dataset for investigation. The method for evaluating and rating risk level of country is based on the Bayesian network which enables prototype to predict risk under uncertain domain.